Energy Efficiency Through Lighting and Cooling System Approach - Mujaahid, Faaris; Mustika, Doane Puri; Syahputra, Ramadoni; Putra, Karisma Trinanda; Purwanto, Kunnu (Journal of Electrical Technology UMY, 2018)
This work reports the implementation of using energy efficient electronic devices to reduce the electricity consumption in Universitas Muhammadiyah Yogyakarta (UMY). The first step taken by UMY is to replace lighting and cooling system in all its rooms using energy saving devices. This research was conducted in building E4. This research was conducted by surveying the designated building to get data about lighting and air conditioner devices used in the E4 building. If the proposed concept is applied to lighting and cooling system, UMY would be able to reduce electricity consumption by 28.1 MWh, and this can support the breakthrough of turning UMY into a green campus.